WORKING SIDE EFFECT OF EDUCATION COLLEGE FACULTY STUDENT UNIVERSITY TEACHING AND EDUCATION JEMBER - Vika Aurely Nalurita (MAJALAH PEMBELAJARAN GEOGRAFI, 2019)
This study aims to analyze the impact of their work on a part-time sideline learning activities and academic achievement. The study population was a student of Faculty of teacher training and education science education geography class B Education in 2019, the State University of Jember. 20 samples were selected using random proportional approach sampling.Para working students have a lower time to learn than non-working student. working student achievement is lower than students of non-kerja.Metode used in this study is survey.Metode it is a method that directly to the existence of a fenomena.Sebagai improvers in understanding the phenomenon also carried out a questionnaire and wawancara.Kuesioner used in an attempt to get The primary data of a research student. References NURDIN, Elan Artono et al. DEMOGRAPHIC FACTORS INFLUENCE ON POPULATION ADDED IN SUMBERSARI JEMBER DISTRICT.Geosfera Indonesia, [S.l.], v. 2, n. 1, p. 60-66, apr. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/7515>. Date accessed: 19 june 2019. doi: https://doi.org/10.19184/geosi.v2i1.7515. KURNIANTO, Fahmi Arif et al. GEOGRAPHIC INFORMATION SYSTEM (GIS) APPLICATION TO ANALYZE LANDSLIDE PRONE DISASTER ZONE IN JEMBER REGENCY EAST JAVA.Geosfera Indonesia, [S.l.], v. 2, n. 1, p. 45-53, apr. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/7524>. Date accessed: 19 june 2019. doi: https://doi.org/10.19184/geosi.v2i1.7524. SARI, Eva Kurnia; PRAMESTY, Dinda Ayu. THE EFFECT OF VEHICLES INTENSITY IN SUMBERSARI JEMBER REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 3, p. 50-58, jan. 2019. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/9300>. Date accessed: 19 june 2019. doi: https://doi.org/10.19184/geosi.v3i3.9300. KURNIANTO, Fahmi Arif et al. THE ENVIRONMENT ANALYSIS OF POPULATION GROWTH, UNEMPLOYMENT, AND POVERTY LEVEL IN MAESAN DISTRICT BONDOWOSO REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 2, p. 113-121, aug. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/8439>. Date accessed: 19 june 2019. doi: https://doi.org/10.19184/geosi.v3i2.8439. Ikhsan, F., Kurnianto, F., Nurdin, E., & Apriyanto, B. (2018). GEOGRAPHY LITERACY OF OBSERVATION INTRODUCTION LANDSCAPE REPRESENTATION PLACE FOR STUDENT EXPERIENCE. Geosfera Indonesia, 3(2), 131-145. doi:10.19184/geosi.v3i2.8384